Modelling the risk of transfusion‐transmitted syphilis: a reconsideration of blood donation testing strategies. Issue 2 (18th December 2018) - Jayawardena, Thisuri; Hoad, Veronica; Styles, Claire; Seed, Clive; Bentley, Peter; Clifford, Vanessa; Lacey, Sarina; Gastrell, Tessa
Abstract : Background and Objectives: Donor syphilis testing began in the 1940s amidst widespread transfusion‐transmitted syphilis (TTS). Since then, the introduction of penicillin, pre‐donation screening questionnaires and improved storage conditions have contributed to reducing transmission risk. Consequently, universal testing may no longer be cost‐effective. This study analysed alternative options for donor syphilis testing to determine the optimal strategy. Materials and Methods: A model was developed using conservative parameter estimates for factors affecting TTS and 2009‐2015 Australian donations to calculate risk outcomes (TTS infections, tertiary syphilis in recipients and transfusion‐associated congenital syphilis) and cost‐effectiveness of alternative testing strategies. The strategies modelled were as follows: universal testing, targeted‐testing of high‐risk groups (males ≤50 years old and first‐time donors) and no testing. Results: The estimated risk of TTS is one in 49·5 million transfusions for universal testing, one in 6 million for targeted‐testing of males ≤50 years old, one in 4 million for targeted‐testing of first‐time donors and one in 2·8 million for no testing. For all strategies, the risk of tertiary and congenital syphilis is <1 in 100 million. Universal testing is the least cost‐effective strategy with an incremental cost‐effectiveness ratio (ICER) estimated at $538·5 million per disability‐adjusted life year averted. Conclusion: Universal testing is not required to maintain the risk of TTS within tolerable limits and is estimated to greatly exceed acceptable ICERs for blood safety interventions. However, despite a strong economic and risk‐based rationale, given the epidemiology of syphilis in Australia is changing, feedback from critical stakeholders is not currently supportive of reducing testing.